Speech By DYTM Tuanku Syed Faizuddin Putra Ibni Tuanku Syed Sirajuddin Jamalullail at the official dinner held in conjunction with the visit by United Nations Environment Programme International Panel Members - DYTM Tuanku Syed Faizuddin Putra Ibni Tuanku Syed Sirajuddin Jamalullail (2009)
Majlis berlangsung di Istana Arau, Perlis